Calidad de Atención percibida por los usuarios del Establecimiento de salud del caserío De Bello Horizonte en el distrito de la Banda de Shilcayo. Junio – Setiembre 2014 - Garay Torres, Cynthia Paola (2014)
The present study aimed to determine the quality of care from the perception of The users of the health facility in the village of Belo Horizonte in the District of The Banda de Shilcayo. June - September 2014 "; quantitative, descriptive, Prospective study of cross-section of design "descriptive simple"; with a sample Of 119 users community members; and for which it applied as instrument of Collection of data, a questionnaire adapted from a package of study of MINSA And validated by expert opinion. Arrived at the following results: the Interpersonal dimension, the majority of users have a unsatisfactory perception (61%) to the quality of care provided by health workers in the dimension of the Environment (comfort), most users have a unsatisfactory perception (71%); in The technical dimension, the majority of external users have a satisfying Perception (82%), about the quality of care provided by the health staff; Concluding that the quality of service perceived by the users in the Establishment of the village of Bello Horizonte health is 50% satisfactory and 50% unsatisfactory.